Disparity of apoptotic response in human breast cancer cells lines MCF-7 and MDA-MB-231 after infection with recombinant adenovirus encoding the VP2 gene of infectious bursal disease virus - Tan, Seok Shin; Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Abdul Rahman, Sheikh Omar (Pleiades Publishing, 2014)
Recombinant adenovirus encoding the VP2 gene of infectious bursal disease virus (ADV-VP2) has shown potent anti-tumour effects due to its capability of apoptotic induction in cancer cells. In the present study, human breast cancer cells MCF-7 and MDA-MB-231 were infected with ADV-VP2. The expression of VP2 protein was registered 4 hours post-infection, particularly in MCF-7 cells. Multiple time-point DNA ladder assay demonstrated that ADV-VP2 infected MDA-MB-231 and MCF-7 cells endured apoptosis as early as 8- and 12- hours post-infection, respectively. Apoptosis induction in both MDA-MB-231 and MCF-7 cells, albeit different start points, lasted until 36-hours post-infection. The induction of apoptosis by ADV-VP2 was further shown by the TUNEL assay, with dark brown discoloration of apoptotic cells. The present study also explored the different stages of apoptosis by Annexin V/PI double staining flow cytometry quantification. Treated MCF-7 and MDA-MB-231 cells, respectively detected 25.58 ± 9.02% and 14.51 ± 3.12% of early apoptotic cells, 6.09 ± 4.06% and 77.12 ± 5.09% of late apoptotic cells. Results revealed that there were significant differences in the number of cells of both types which underwent early and late apoptosis. Significant differences were also observed among viable and apoptotic cells which have been post treated with ADV-VP2. The apoptotic effects of ADV-VP2 on human breast cancer cell lines were consistently demonstrated by three apoptosis detection methods. Therefore, a cancer vaccine basing on gene therapy could be developed in the near future using the present construct.